2014
DOI: 10.1007/s00468-014-1076-0
|View full text |Cite
|
Sign up to set email alerts
|

Determining parameters related to the likelihood of failure of red oak (Quercus rubra L.) from winching tests

Abstract: Key message This study provides data necessary to develop mechanistic models of the failure of opengrown trees. The literature contains few such data. Some results contrast previous studies on conifers. Abstract In cities and towns, tree failure can cause damage and injury. Few studies have considered large, open-grown trees when measuring parameters related to tree failure. To measure elastic modulus and maximum bending moment and stress, we winched red oaks (Quercus rubra L.), including some with co-dominant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…By convention (Smiley et al 2011 ), we considered weakly attached branches as those with a narrow attachment, included bark, visually similar diameters of branch and trunk, or a combination of these. Secondly, for most structural defects of trees, thresholds at which failure is more likely have not been established [see, for example, Kane ( 2014 )]. Regarding the most common defect we observed (weakly attached branches), previous studies have suggested that the strength of a branch attachment decreases (i) as the ratio of the branch and trunk diameters increases (Kane et al 2008 ) and (ii) with the presence of included bark (Smiley 2003 ), and these findings have been consistent among several species (Kane et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By convention (Smiley et al 2011 ), we considered weakly attached branches as those with a narrow attachment, included bark, visually similar diameters of branch and trunk, or a combination of these. Secondly, for most structural defects of trees, thresholds at which failure is more likely have not been established [see, for example, Kane ( 2014 )]. Regarding the most common defect we observed (weakly attached branches), previous studies have suggested that the strength of a branch attachment decreases (i) as the ratio of the branch and trunk diameters increases (Kane et al 2008 ) and (ii) with the presence of included bark (Smiley 2003 ), and these findings have been consistent among several species (Kane et al 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating the severity of some defects, however, is still based largely on experience rather than empirical data. For example, there are very few studies that have quantified the breaking strength of stems of large, open-grown trees with and without defects (Kane and Clouston 2008 ; Kane 2014 ). In urbanized settings, tree failure can damage property and injure persons, which, in the United States, are sometimes associated with costly litigation (Mortimer and Kane 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…While this work was on thin bark samples of 2-4 year old Quercus rubra (L.) stump sprouts, Dahle et al (In Review) believes that with the minimal loading taking place during our sampling, strain measurement with bark intact will be sufficient. Kane (2014) found in pulling tests that bark thickness may not be accounted for. However, Coutts (1983) reports that bark contributed little strength in roots.…”
Section: Barkmentioning
confidence: 99%
“…However, to ensure that the likelihood of tree failure and tissue deformation is minimized, a specific bending moment is needed that will be compatible with the wood materials' Y (proportional limit) and within elastic domain for the tree species. Since there are few published values available for Y for large, open grown trees, (Kane et al 2014), bending moment and Y could be used in conjunction with root-plate tilt data to better quantify the movement of strain across the RSTZ. Brudi and van Wassenaer (2002) have proposed the following stress equation for nondestructive pulling trials, using a bending moment calculation to account for the height of the attachment and the circumference of the cross section of attachment.…”
Section: Bending Momentmentioning
confidence: 99%
“…In summary, although static pull tests and static biomechanics have aided our understanding of how trees handle loads, they use simplifying assumptions which may or may not accurately represent real world loading schemes (Niklas 1992, Hale et al 2010, Dahle et al 2017. For examples of static pull test studies, see: Kane 2014or Peterson & Claassen 2013.…”
Section: Static Pull Testsmentioning
confidence: 99%